Penyelesaian Sengketa Para Pihak di Bidang Bisnis melalui Arbitrase - Nurdin Siregar; Radisman Saragih (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Arbitration is a way of solving civil disputes outside the public courts based the arbitration agreement made in writing by the parties to the dispute. The arbitration agreement is an agreement in the form of the arbitration clause contained in a written agreement made by the parties before a dispute arises or a separate arbitration agreement made by the parties after a dispute arises. In everyday life with various activities of members of today’s society, immense possibility of friction-friction in running business and trade that ended with disputes between members of the public and businesses. In efforts to completion, it would seem that this form of dispute diversity define the core issues then this diversity will be easy settlement with the provisions and rules of law that are sure to be able to look for the solution either arbitration or by mediation, consulting, negotiations, konsialiasi. The arbitration decision will be implemented after the verdict copy officially registered, but the arbitration ruling in accordance with the provisions of the law Arbitration can still be filed annulment if the decision is thought to contain elements, letters or documents are filed in the examination after the verdict recognized dinyataakan counterfeit or fake, after adjudication documents found prescriptive, which is hidden by the other party or the decision taken on the results of a ruse conducted by one of the parties in the dispute. That for legal certainty associated with the judiciary also good for the winning side and the decision is legally binding. Kata Kunci: Penyelesaian sengketa bisnis melalui arbitrase